The Urgency of Imposing Excise Tax on Sweetened Beverages in Packaging (MBDK) as an Instrument for Diabetes Control in Indonesia - Eva Rutnauli Sinaga; Ratih Damayanti (Universitas Negeri Semarang, 2026)
The rising prevalence of diabetes mellitus in Indonesia represents a significant public health concern, particularly in relation to excessive sugar intake. This normative legal research seeks to examine the urgency of establishing excise regulation on sugar-sweetened beverages (SSBs) as a strategic policy instrument for diabetes prevention and control. Using statutory and conceptual approaches, the study finds that although the SSB tax policy has not yet been enforced, it is supported by a solid legal foundation and strong policy justification. Such regulation has the potential to contribute to reducing sugar consumption while also strengthening health financing mechanisms. Accordingly, this research highlights the need to expedite the development and implementation of an SSB excise policy as part of a sustainable national health strategy.